Building resilient clusters through HRM systems: a multiple mediator model. Issue 6 (14th February 2018) - Belso-Martinez, José; Palacios-Marqués, Daniel; Roig-Tierno, Norat
Abstract : Purpose: There is a growing research interest in the relationships between networks and the firm's assets and between networks and innovation. Studies have shown the complexity and idiosyncrasies of these relationships for firms in clusters. The way firms in clusters build certain organizational resources and capabilities, however, remains underexplored. Based on the assumption that most of these organizational assets rely on human resources, the purpose of this paper is to shed light on the mechanisms through which a set of managerial practices (the human resource management (HRM) system) enhances innovation. Design/methodology/approach: Micro-level data were collected for 139 firms located in three Spanish industrial clusters. Next, the main constructs were developed. A multiple mediator model was then used to examine how HRM systems influence innovation through strategic vision, embeddedness in local networks, the implementation of enterprise systems, and cluster characteristics. Findings: The effect of HRM systems on innovation performance was indirect rather than direct. All four mediating variables included in the model were found to be relevant mechanisms through which HRM systems affect innovation performance. The statistical significance of these variables, however, varied depending on the type of innovation (product, process, organizational, or marketing). Practical implications: Greater attention should be paid to the structure and sophistication of HRM systems. Top-level managers should be aware of the linkages between HRM systems and mediators. Greater human resource orientation in strategic planning, enterprise system design, and networking practices reinforces the association between HRM systems and innovation. Originality/value: This study advances our understanding of the mechanisms underlying the relationship between HRM systems and innovation. From an academic perspective, this study enriches the cluster literature by better integrating human resources with innovation processes. Furthermore, this study creates research opportunities by disentangling the role of different managerial practices and refining the operationalization of the mediating variables. The findings can also help managers develop human resources and innovation strategies.